Identificação molecular e filogenética de Leptospira spp. detectados em animais silvestres, pets não convencionais e em gatos domésticos no Rio Grande do Sul, Brasil - Ulsenheimer, Bruna Carolina (2024)
Bacteria of the genus Leptospira are the etiological agents of leptospirosis, a disease responsible for considerable impacts on the economy, public health and animal health, characterized as a zoonosis with worldwide distribution and a high occurrence in Brazil. The etiological agent of leptospirosis is present in rural and urban environments, being transmitted both through direct and indirect contact, especially with the urine of infected animals. In this way, domestic and wild species can become infected with Leptospira spp. and act as a source of infection for other hosts, including humans. Among the domestic species affected, the canine, bovine, equine and swine species stand out; however, in wild animal species and domestic cats there is a lack of studies, especially molecular studies that demonstrate evidence about Leptospira spp. in these animal species. The present study aimed to perform the molecular detection of pathogenic Leptospira spp. DNA in kidney tissue of different animal species, including wild mammals and domestic cats (Felis wild catus) from Rio Grande do Sul (RS), Brazil, in addition, identifying the species of Leptospira spp. present in the kidney tissue of the animals studied. The samples in this study were evaluated for the presence of lipL32 gene by polymerase chain reaction (PCR), followed by sequencing of the amplified fragment and phylogenetic analyses. Total DNA from Leptospira spp. was extracted from the kidney tissue of wild animals (class Mammalia) and domestic cats from RS, Brazil. As a result of this research DNA of pathogenic Leptospira spp. was detected in 9.6% (11/114) of wild animal samples, from nine different species of mammals, including the whiteeared opossum (Didelphis albiventris) at 18.2% (2/11), skunk (Conepatus chinga) at 18.2% (2/11), geoffroy’s cat (Leopardus geoffroyi) at 9.1% (1/11), margay (Leopardus wiedii) at 9.1% (1/11), pampas fox (Lycalopex gymnocercus) at 9.1% (1/11), capybara (Hydrochoerus hydrochaeris) at 9.1% (1/11), common marmoset (Callithrix jacchus) at 9.1% (1/11), neotropical river otter (Lontra longicaudis) at 9.1% (1/11), and european hare (Lepus europaeus) at 9.1% (1/11). In unconventional pets, DNA from pathogenic Leptospira spp. was detected in 13.8% (4/29) of samples from two of the five species analyzed, corresponding to rabbit (Oryctolagus cuniculus) with 75% (3/4) and the hamster (Mesocricetus auratus) with 25% (1/4). In domestic cats (Felis silvestris catus) the presence of pathogenic Leptospira spp. was detected in 22.1% (67/303) of the samples analyzed. After DNA sequencing and phylogenetic analysis, the presence of two pathogenic species, Leptospira borgpetersenii and Leptospira interrogans, was demonstrated. This research is pioneering, contributing to the epidemiology of leptospirosis by identifying L. interrogans and L. borgpetersenii in wild mammals and domestic cats in RS, Brazil. The findings of this study highlight the importance of these animal species that can serve as potential reservoirs for Leptospira spp. Furthermore, the need to include these species in monitoring the epidemiology of this relevant zoonosis is emphasized, aiming to guide effective measures to control and prevent leptospirosis, especially in endemic areas, contributing to the promotion of One Health.